Family caregivers' perspectives on barriers to caring for patients with schizophrenia: A descriptive qualitative study - Masoumeh Asgari; Masoomeh Adib; Nahid Dehghan Nayeri; Fatemeh Rezayat (Tehran University of Medical Sciences, 2023)
Background & Aim: Schizophrenia significantly burdens family members when a member of their family is afflicted with this condition. Family caregivers play a pivotal role in providing care and support to individuals experiencing schizophrenia within the community. Therefore, an in-depth study of family caregivers' experiences is crucial for developing effective care quality improvement programs. This study aimed at exploring family caregivers' experiences of the barriers to caregiving to patients with schizophrenia. Methods & Materials: This study was conducted in 2021-2022 through in-depth semi-structured. The duration of the interviews varied in length from 45 to 90 minutes. Interviews were conducted with sixteen family caregivers of patients with schizophrenia. The conventional content analysis proposed by Graneheim and Lundman was used for data analysis. Results: The findings can be classified into three primary categories. The category "Inefficiency of Support Resources" encompasses the subcategories of "Inadequate Support by Family Members," "Inadequate Support by the Healthcare System," and "Financial Predicament." The category "Limited Public Knowledge about Psychiatric Disorders" includes the subcategories of "Social Stigmatization" and "Being Social Rejection." Lastly, the category "destructive nature of schizophrenia" encompasses the subcategories of "Gradual Loss of Abilities" and "Gradual Patient Passivity." Conclusion: Family caregivers encounter various barriers in providing patient care. Thus, they require support from the treatment team and family members, as well as financial and the development of rehabilitation programs. Additionally, involving caregivers in the patient's treatment plan and planning programs to reduce the stigma associated with caregivers is crucial.